The Influence of Quality of Work Life (QWL) on Employees’ Organizational Commitment - Syamsuddin Syamsuddin; Abdul Kadir; Samrin; Yunita Andriani (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2020)
Employees’ organizational commitment refers to the individuals’ loyalty and involvement in all institution activities. Therefore, the variable becomes fundamental in a higher education institution. It indicates the need for the institution to improve the work life quality. The present study aimed to know and analyze the influence of QWL on the employees’ organizational commitment. The quantitative research was conducted in State Islamic Institute (IAIN) Kendari in 2019 with 55 samples out of 142 population. The precision was 10%. The findings showed that QWL has a positive and significant influence, reaching a score of 0.727 or 72.7%. It means that the employees’ commitment can be increased by improving the Quality of Work Life (QWL).